Myelin-associated glycoprotein and myelinating Schwann cell-axon interaction in chronic B,B'-iminodipropionitrile neuropathy (The Rockefeller University Press, 1984)
The myelin-associated glycoprotein (MAG) is a heavily glycosylated integral membrane glycoprotein which is a minor component of isolated rat peripheral nervous system (PNS) myelin. Immunocytochemically MAG has been localized in the periaxonal region of PNS myelin sheaths. The periaxonal localization and biochemical features of MAG are consistent with the hypothesis that MAG plays a role in maintaining the periaxonal space of myelinated fibers. To test this hypothesis, MAG was localized immunocytochemically in 1-micron sections of the L5 ventral root from rats exposed to B,B'-iminodipropionitrile. In chronic states of B,B'- iminodipropionitrile intoxication, Schwann cell periaxonal membranes and the axolemma invaginate into giant axonal swellings and separate a central zone of normally oriented axoplasm from an outer zone of maloriented neurofilaments. Ultrastructurally, the width of the periaxonal space (12-14 nm) in the ingrowths is identical to that found in normally myelinated fibers. These Schwann cell ingrowths which are separated from compact myelin by several micra are stained intensely by MAG antiserum. Antiserum directed against Po protein, the major structural protein of compact PNS myelin, does not stain the ingrowths unless compact myelin is present. These results demonstrate the periaxonal localization of MAG and support a functional role for MAG in maintaining the periaxonal space of PNS myelinated fibers.